1988
DOI: 10.1159/000120388
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Intracranial and Sagittal Sinus Pressure in Normal and Hydrocephalic Dogs

Abstract: The relationship between intracranial and sagittal sinus pressure in normal and kaolin-induced hydrocephalic greyhounds was examined. In normal dogs there was an average 14 mm Hg pressure difference between the ventricles and the sagittal sinus. Elevations of intraventricular pressure were accompanied by small but consistent elevations in sagittal sinus pressure. In hydrocephalic dogs the average pressure differential was only 2 mm Hg. Also elevations of intraventricular pressure were accompanied by greater el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 10 publications
4
38
0
1
Order By: Relevance
“…The normal gradient is 2-14 cm H 2 O [17][18][19]. Flexner found the normal ratio of subarachnoid pressure to sagittal sinus pressure to be approximately 1.7:1 [6].…”
Section: Pressure Gradient From the Subarachnoid Space To The Dural Vmentioning
confidence: 99%
See 1 more Smart Citation
“…The normal gradient is 2-14 cm H 2 O [17][18][19]. Flexner found the normal ratio of subarachnoid pressure to sagittal sinus pressure to be approximately 1.7:1 [6].…”
Section: Pressure Gradient From the Subarachnoid Space To The Dural Vmentioning
confidence: 99%
“…In clinical and experimental hydrocephalus, both subarachnoid and venous pressures rise, but there is a narrowing, not a widening, of the pressure gradient across the arachnoid villi [6,[18][19][20][21]. Shulman et al [19] found that the average pressure gradient of 57 mm H 2 O between the subarachnoid space and sagittal sinus in normal dogs diminished to 2 mm H 2 O in dogs made hydrocephalic by kaolin.…”
Section: Pressure Gradient From the Subarachnoid Space To The Dural Vmentioning
confidence: 99%
“…4 In cases of IIH in which there is a high suspicion of sinus thrombosis, procedures such as conventional cerebral angiography, direct retrograde cerebral venography, and manometry are performed to characterize their morphological features and venous pressures, to perform a therapeutic balloon venoplasty or endoluminal venous sinus stenting if necessary. 4,16,[30][31][32] Although most children with IIH improve with medical treatment, those who have had visual progression despite medical treatment have undergone optic nerve sheath fenestration and lumboperitoneal shunting or even ventriculoperitoneal shunting in certain cases. 38 All patients reported on in our series were of similar age and body habitus, and all had a preexisting spinal deformity.…”
Section: Discussionmentioning
confidence: 99%
“…CSF absorption depends on the pressure gradient across the subarachnoid space and the sagittal sinus; therefore, any increase in the sinus pressures produced by the vascular malformation would need to be matched by the CSF pathways. Ventricular enlargement occurs as a compensatory mechanism involved in increasing CSF pressure to maintain a gradient of 5–7 mm Hg [15,16]. …”
Section: Discussionmentioning
confidence: 99%